Dental clinic. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows dental clinic at Portland, Oregon Assembly Center with evacuees being examined by Japanese dentists. The Portland Assembly Center was formerly known as the North Portland International Livestock Exposition Center.